Rehabilitation in the new juvenile court: Do judges support the treatment ethic? - Bazemore, Gordon (American journal of criminal justice, 1997)
This article uses data from a statewide survey of Florida juvenile court judges to examine support for the rehabilitative ethic. Descriptive findings reveal strong support for rehabilitation as an overall goal for the juvenile justice system and the treatment ideal as a focus of staff efforts. In an effort to account for variation between judges in intensity of this support, we compared four explanatory models — ideological influences, organizational environment, court work group, and individual experiences importation. Neither ideological influences nor individual experiences indicators (with the exception of number of years as a judge) contribute to explained variance in support for rehabilitation. Rather, the organizational environment variables and one court work group indicator (having similar views as other judges) account for the greatest relative impact on the dependent variable.